Post-Cataract Surgery Fungal Endophthalmitis: 6-Year Experience in Management and Outcomes at a Tertiary Eye Care Center - Aloqab A; Semidey VA; Sesma G; AlYahya A; Al Malki K; Al Yahya A; Alohali RM; AlShareef M; Al-Dhibi HA (Clinical Ophthalmology)
Aysha Aloqab,1,2 Valmore A Semidey,1 Gorka Sesma,3 Abdulmalik AlYahya,1 Khaled Al Malki,1 Abdulrahman Al Yahya,4 Rawa Mosaed Alohali,4 Mozon AlShareef,5 Hassan A Al-Dhibi1 1Vitreoretinal Division, King Khaled Eye Specialist Hospital, Riyadh, Saudi Arabia; 2Ophthalmology, Bahrain Defence Force Hospital, Riffa, Bahrain; 3Pediatric Ophthalmology and Strabismus Division, King Khaled Eye Specialist Hospital, Riyadh, Saudi Arabia; 4Fellowship and Residency Training Program, King Khaled Eye Specialist Hospital, Riyadh, Saudi Arabia; 5Medicine Department, King Khaled Eye Specialist Hospital, Riyadh, Saudi ArabiaCorrespondence: Valmore A Semidey, King Khaled Eye Specialist Hospital, Al Urubah Road, Riyadh, 12329, Kingdom of Saudi Arabia, Tel +96614281234 ext. 2665, Fax +966114821234 ext. 3773, Email asemidey@hotmail.comPurpose: This study aimed to describe the functional and anatomical outcomes of post-cataract surgery fungal endophthalmitis at King Khaled Eye Specialist Hospital (KKESH).Patients and Methods: A retrospective analysis of clinical data from a single institution was performed. This study included 29 patients with post-cataract surgery endophthalmitis with suspected or confirmed fungal etiology who presented between January 1, 2017, and December 31, 2022. We evaluated demographics, clinical features, microbiological assessments, and treatment strategies. The effects of various treatments on outcomes were analyzed. The need for additional treatment and functional and anatomical outcomes was also investigated.Results: The mean time from surgery to the onset of ocular symptoms was 52.1 (SD ± 59.9; range, 3– 210) days, and the mean time from surgery to the first visit to KKESH was 81.4 (SD ± 103.5; range, 2– 510) days. Low culture positivity was noted in four samples, with two revealing Aspergillus sp. and two revealing Cladosporium sp. Of the 29 patients, 6 underwent pars plana vitrectomy (PPV) and received intravitreal antimicrobial/antibiotic injections. Two of the six patients also underwent simultaneous intraocular lens removal. The average number of additional treatments, regardless of visual acuity, was lower in the PPV group than in the conservative group (0.5 [SD ± 1.1; range, 0– 3] and 1.48 [SD ± 1.47; range, 0– 6], respectively). In the PPV group, 50% (n=3) of the eyes achieved functional success and 83.3% (n=5) of the eyes achieved anatomical success. In contrast, in the conservative group, 43.5% (n=10) of the eyes achieved functional success and 69.6% (n=16) of the eyes achieved anatomical success.Conclusion: For post-cataract surgery fungal endophthalmitis, a high index of suspicion and prompt PPV with empirical administration of intravitreal antifungal agents are required to achieve a favorable prognosis.Keywords: endophthalmitis, fungal, exogenous, pars plana vitrectomy, intraocular lens removal